The potential of authentic learning and emerging technologies for developing graduate attributes - Bozalek, Vivienne; Watters, Kathy (South African Journal of Higher Education, 2016)
Graduate attributes such as critical thinking and problem-solving in real world contexts are increasingly being recognised as crucial for students to develop in higher education for employability and critical citizenship. The question of how best to create conducive spaces in the curriculum for students to acquire these abilities is however less well documented. We propose that one way to enable students to achieve these attributes would be for higher educators to engage in authentic learning, using Herrington et al.’s (2010) model as a guide. In this article, one case study is selected from a sample of ten interviews of University of the Western Cape lecturers as it rated highly on all nine elements of authentic learning. The curriculum design and teaching and learning practices are analysed using each of Herrington et al.'s elements for authentic learning and the potential of these elements for developing graduate attributes is considered.